Informational support needs of pregnant women and new mothers in Cyprus and information-seeking practices on the internet during the transition to parenthood: a mixed-methods exploratory study - Koliandri, Ioanna (My University, 2024)
Background: The transition to parenthood (TtP) is a significant and challenging period characterized by rewards but also numerous stressors. In addition to good quality medical care, women need relevant and timely information to support their decision-making process. Traditional approaches to antenatal education have been questioned as to their effectiveness to the extent to which they address the real informational needs of pregnant women. The use of the internet for information-seeking is widespread among women; however, the process is mostly unguided and can at times be stressful. While there is no shortage of information on pregnancy and childbirth online, the quality and accuracy of the information varies. While women would benefit from discussing information retrieved online with their healthcare providers, studies have suggested that health professionals remain reluctant to incorporate this reality into routine practice. Aim: To explore the informational support of women in Cyprus during TtP as well as their expectations, experiences and information-seeking practices, with a focus on the use of the Internet in the context of assisting informed decision-making. Methods: This was a mixed-methods descriptive sequential exploratory study (QUAL→Quant). A series of focus groups provided an in-depth understanding of women’s’ experiences in terms of their informational support needs and information-seeking practices, including the use of the internet for information. This was followed by a quantitative web-based survey among pregnant women and new mothers to quantify the characteristics and important aspects of internet use during TtP as well as to explore further some important constructs that emerged from the qualitative study related to user-provider interactions in the context of informed decision-making. The qualitative study involved 12 focus groups with 64 participants representing different language-cultural groups. A semi-structured interview guide was used covering the expectations, experiences and information seeking practices during pregnancy. The data were analyzed using inductive content analysis. The survey (N=387) focused on the use of the internet in pregnancy, perceptions of trustworthiness, critical appraisal skills and the perceived role of the internet in assisting decision making, based on questionnaires adapted accordingly from similar previous studies. Furthermore, the context, process and outcomes of the user-provider interaction were explored, namely, the perceived self-efficacy in user-provider (as measured according to the PEPPI scale), the perceived alliance with healthcare providers (as measured by the Kim Alliance Scale (KAM), the perceived autonomy in decision making (as measured by the Maternal Autonomy in Decision-Making – MADM scale. Descriptive analysis was performed for each of the variables under investigation and differences according to socio-demographic and pregnancy-related characteristics were explored. Correlational and regression analysis was employed to explore associations of user-provider interaction variables with autonomy in decision-making. The data were analyzed using SPSSv25 (Statistical Package for Social Sciences). Results: Seven themes and several sub-themes emerged from the qualitative data. In an “unsupportive system”, ‘void’ of informational support, pregnant women strive to have a “confident voice”. They find themselves “self-navigating in parallel worlds” of formal and informal information, where the internet holds a prominent place. “Supplementing and filtering”, most commonly instinctively and selectively, results in a state of “doubt and faith” towards the trustworthiness of the information but also towards healthcare providers. Effective communication with providers is needed to break the cycle, but this seems dependent on the self-efficacy of the women themselves (“art of communication”). While women “de-construct and re-imagine” their experiences, they often assign responsibility on themselves for not having been better prepared. Among 387 participants in the survey (32.6% pregnant, 67.4% new mums, 63.6% primiparas, 42.6% C/S, 79.6% private sector), searching online for information about pregnancy, childbirth and parenting seems very frequent, even though 65.1% of them report coming across wrong or misleading information often. Cross-checking for consistency across sites and/or with information by healthcare providers (92.8%) is the most common technique for assessing trustworthiness. As many as 87.9% of survey participants believe that healthcare professionals should recommend trustworthy internet sites, but only 6.5% report that their HP made recommendations. Even though women report discussing information retrieved from the internet with their Healthcare providers, as many as 38.7% of the women characterize the healthcare provider’s reception as negative (e.g. ignored or dismissed the information and/or recommended not to use the internet) or the women themselves chose not discuss this information with them. The role of the internet in assisting decision-making is rated by women as moderate (M=2.29, SD=0.57); yet 57.6% of participants reported searching online in order to have control over their decisions. In terms of autonomy in decision-making, this was classified as high for 54.3%% of the women in the survey, based on their responses on the MADM scale, while 21% of the women were classified as having low or very low levels of autonomy. Higher scores of autonomy were linked to multiparous women (p=0.02) and women giving birth in the private sector (p<0.001). Higher levels of mother's autonomy in decision-making were linked to lower levels of internet use, but the correlation was only weak (r=-0.15, p<0001). Strong positive correlations were observed with the perceived efficacy in patient-physician interaction (r=0.60, p<0.001) and perceived alliance with healthcare providers (r=0.71, p<0.001). Conclusion: Women want to have control over decisions affecting their pregnancy but their informational needs do not seem to be supported by current healthcare practices. While the internet is a prevalent information source, the flow of information is problematic as it appears that women are more likely to search online to verify information rather than discuss this information with their providers, who do not always welcome or encourage it. Women, nevertheless, value communication with their healthcare providers and expect informational support and guidance.; but there are major gaps in user-provider communication and the experience seems to be dependent on the women’s self-efficacy and the responsiveness from healthcare providers The insights from this mixed-method study suggest that maternity healthcare professionals need to recognize women’s’ need for informational support and engage with women in an educational capacity during routine appointments. The educational role is an indispensable part of their professional role and responsibility in order to support women’s right to informed decision-making. As the internet has a prevalent role in women’s information-seeking practices, a process that is often stressful, healthcare providers should recognize the phenomenon, rather than ignore or discourage it. Embracing the new digital era of information, health professionals should actively encourage open communication with women regarding information they retrieved from the internet. This would allow health professionals to gain insights to women's concerns, needs and preferences while guiding them to reliable websites or other digital sources of information to empower women and support shared decision-making.
Keywords: pregnancy; motherhood; transition to parenthood; informational needs; informational support; information seeking; internet; informed decision-making